Interprofessional faculty development: integration of oral health into the geriatric diabetes curriculum, from theory to practice - Dounis G (Journal of Multidisciplinary Healthcare, 2013)
Georgia Dounis,1 Marcia Ditmyer,2 Susan VanBeuge,3 Sue Schuerman,4 Mildred McClain,1 Kiki Dounis,1,5 Connie Mobley21Department of Clinical Sciences, 2Department of Biomedical Sciences, 3Department of Physiological Nursing, 4Department of Physical Therapy, University of Nevada Las Vegas School of Dental Medicine, Las Vegas, NV, USA; 5Department of Family Medicine, University of Nevada School of Medicine, Reno, NV, USABackground: Health care workforce shortages and an increase demand for health care services by an older demographic challenged by oral–systemic conditions are being recognized across health care systems. Demands are placed on health care professionals to render coordinated delivery of services. Management of oral–systemic conditions requires a trained health care workforce to render interprofessional patient-centered and coordinated delivery of health care services. The purpose of this investigation was to evaluate the effectiveness of an interprofessional health care faculty training program.Methods: A statewide comprehensive type 2 diabetes training program was developed and offered to multidisciplinary health care faculty using innovative educational methods. Video-recorded clinically simulated patient encounters concentrated on the oral–systemic interactions between type 2 diabetes and comorbidities. Post-encounter instructors facilitated debriefing focused on preconceptions, self-assessment, and peer discussions, to develop a joint interprofessional care plan. Furthermore, the health care faculty explored nonhierarchical opportunities to bridge common health care themes and concepts, as well as opportunities to translate information into classroom instruction and patient care.Results: Thirty-six health care faculty from six disciplines completed the pre-research and post-research assessment survey to evaluate attitudes, knowledge, and perceptions following the interprofessional health care faculty training program. Post-training interprofessional team building knowledge improved significantly. The health care faculty post-training attitude scores improved significantly, with heightened awareness of the unique oral–systemic care needs of older adults with type 2 diabetes, supporting an interprofessional team approach to care management. In addition, the health care faculty viewed communication across disciplines as being essential and interprofessional training as being vital to the core curriculum of each discipline. Significant improvement occurred in the perception survey items for team accountability and use of uniform terminology to bridge communication gaps.Conclusion: Attitude, knowledge, and perceptions of health care faculty regarding interprofessional team building and the team approach to management of the oral–systemic manifestations of chronic disease in older adults was improved. Uniform language to promote communication across health professionals, care settings, and caregivers/patients, was noted. Interprofessional team building/care planning should be integrated in core curricula.Keywords: team building, patient-centered care, oral–systemic, older adults